Unveiling the Complete Chloroplast Genome of Tribulus Macropterus Var. Arabicus (Hosni) Al-Hemaid & J. Thomas: Genome Structure, Comparative Analysis and Phylogeny - Albediwi, Albatool Suliman; Ali, Mohammad Ajmal; Alwahibi, Mona Solaiman; Ahmed, Sheikh Sunzid; Rahman, M Oliur; Kim, Soo Yong; Elshikh, Mohamed S; Alsuhaimi, Nadia Mohammad (Bangladesh Journal of Plant Taxonomy, 2024)
The present investigation unveiled the first complete chloroplast (cp) genome of Tribulus macropterus var. arabicus (Hosni) Al-Hemaid & J. Thomas (Zygophyllaceae), a medicinal herb, indigenous to Saudi Arabia. The cp genome, comprising a length of 158,179 bp and a GC content of 35.8%, exhibited the typical circular quadripartite arrangement of flowering plants, including two inverted repeat regions (25842 bp) separated by a large single-copy (88873 bp) and a small single-copy region (17622 bp). Genome annotation unraveled 132 genes, comprising of 87 protein-coding genes, 37 tRNAs and eight rRNAs. A comparative plastomics approach demonstrated a very similar genome structure and gene organization in closely related taxa. Whole-genome alignment indicated that the inverted repeat regions exhibited greater conservation when compared to the single copy zones. Repeat analysis of the cp genome identified 80 simple sequence repeats, with the majority (64) being mononucleotides. Among the longer repeats, forward repeats were frequent (20) followed by palindromic and reverse repeats. The nucleotide diversity endeavor identified some hypervariable sites (rpl22, cemA, trnL-UAG) in the small and large single copies which would offer opportunities to design molecular markers for potential application in taxonomic identification. Phylogenetic analysis with rbcL barcode elucidated the distinct position of T. macropterus var. arabicus compared to T. macropterus within Zygophyllaceae and further validated the assembly. The findings of this investigation provide significant insights into biological fields, particularly enhancing the current understanding of the genetic and evolutionary variations within Zygophyllaceae. Bangladesh J. Plant Taxon. 31(1): 1-14, 2024 (June)